Elementos para el estudio de una migración antigua: el caso de los Chorotega-Mangue - Salgado González, Silvia (2015)
Here we conduct a conceptual exercise, using already documented cases from Northwestern Costa Rica and Pacific Nicaragua, to present an interpretative model of how the migration process of the Chorotega-Mangue could have taken place. This has been a recurrent theme in the archeology of the region since the first scientific archaeological investigations were carried out in the 1950's.